Genetic diversity of bromeliaceae species from the atlantic forest - Sheu, Yumi; Cunha-Machado, Antônio Saulo; Gontijo, Andreia Barcelos Passos Lima; Favoreto, Fernanda Campanharo; Soares, Taís Cristina Bastos; Miranda, F. D. (Genetics and Molecular Research, 2017)
The Bromeliaceae family includes a range of species used for many purposes, including ornamental use and use as food, medicine, feed, and fiber. The state of Espírito Santo, Brazil is a center of diversity for this family in the Atlantic Forest. We evaluated the genetic diversity of five populations of the Bromeliaceae family, including specimens of the genera Aechmea, Billbergia (subfamily Bromelioideae), and Pitcairnia (subfamily Pitcairnioidea), all found in the Atlantic Forest and distributed in the state of Espírito Santo. The number of alleles per locus in populations ranged from two to six and the fixation index (F), estimated for some simple sequence repeats in bromeliad populations, was less than zero in all populations. All markers in the Pitcairnia flammea population were in Hardy-Weinberg equilibrium (P < 0.05). Moreover, significant deviations from Hardy-Weinberg equilibrium were observed at some loci in populations of the five bromeliad species. In most cases, this can be attributed to the presence of inbreeding or the Wahlund effect. The genetic diversity indices of five species showed greater allelic richness in P. flammea (3.55). Therefore, we provide useful information for the characterization of genetic diversity in natural populations of Aechmea ramosa, Aechmea nudicaulis, Billbergia horrid, Billbergia euphemia, and P. flammea in Atlantic Forest remnants in the south of Espírito Santo state. © 2017 The Authors.
Keywords: Allele; Bromeliaceae; Family; Forest; Genetic Variability; Human; Human Experiment; Inbreeding; Natural Population; Nonhuman; Simple Sequence Repeat; Species; Biodiversity; Bromeliaceae; Classification; Gene Locus; Polymorphism, Genetic; Genetics; Alleles; Biodiversity; Bromeliaceae; Forests; Genetic Loci; Inbreeding; Polymorphism, Genetic